A novel technique for detoxification of phenol from wastewater: Nanoparticle Assisted Nano Filtration (NANF). Issue 1 (December 2016) - Naidu, L.; Saravanan, S.; Goel, Mukesh; Periasamy, S.; Stroeve, Pieter
Abstract Background Phenol is one of the most versatile and important organic compound. It is also a growing concern as water pollutants due to its high persistence and toxicity. Removal of Phenol from wastewaters was investigated using a novel nanoparticle adsorption and nanofiltration technique named as Nanoparticle Assisted Nano Filtration (NANF). Methods The nanoparticle used for NANF study were silver nanoparticles and synthesized to three distinct average particle sizes of 10 nm, 40 nm and 70 nm. The effect of nanoparticle size, their concentrations and their tri and diparticle combinations upon phenol removal were studied. Results Total surface areas (TSA) for various particle size and concentrations have been calculated and the highest was 4710 × 1012 nm2 for 10 nm particles and 180 ppm concentration while the lowest was for 2461 × 1011 for 70 nm and 60 ppm concentrations. Tri and diparticle studies showed more phenol removal % than that of their individual particles, particularly for using small particles on large membrane pore size and large particles at low concentrations. These results have also been confirmed with COD and toxicity removal studies. Conclusions The combination of nanoparticles adsorption and nanofiltration results in high phenol removal and mineralization, leading to the conclusion that NANF has very high potential for treating toxic chemical wastewaters.